VALUE FOUNDATIONS OF SCIENTIFIC KNOWLEDGE (Conference Review) - Galina L. Belkina; Sergey N. Korsakov (Высшее образование в России)
The 15th Frolov Readings, Science Conference was held on December 1, 2015 at the RAS Institute ofPhilosophy. I.T. Frolov was the founder of the integrated interdisciplinary approach to Human studies in philosophy and science in Russia. Philosopher became the initiator of creating of the RAS Institute of Human studies, which united the researchers in different areas. Academician I.T. Frolov considered human values to be the key regulative principles of cognition in the age when science has entered the "anthropology century". The value factor has a special significance in techno-science, which touches the biological foundations of human existence. The consequences of interference in genome, physiology, human mentality can be irreversible and fatal. This range of complex problems was discussed at the annual Frolov Readings.